Well-defined palladium(0) complexes bearing N-heterocyclic carbene and phosphine moieties: efficient catalytic applications in the Mizoroki–Heck reaction and direct C–H functionalization. Issue 25 (2nd June 2016) - Lee, Jhen-Yi; Shen, Jiun-Shian; Tzeng, Ru-Jiun; Lu, I-Chen; Lii, Jenn-Huei; Hu, Ching-Han; Lee, Hon Man
Abstract : A well-defined palladium(0) complex with a phosphine-functionalized N-heterocyclic carbene ligand was prepared and shown to be inefficient in catalyzing Mizoroki–Heck coupling and direct C–H functionalization reactions. Abstract : Two series of well-defined palladium(0) complexes with phosphine-functionalized N-heterocyclic carbene ligands were prepared. These complexes featured six- and seven-membered chelate rings in the two series. Among the seven-membered chelate complexes, those featuring the PCy2 moiety exhibited observable fluxional behavior on the NMR time scale, corresponding to the interchange between two sets of conformations. Most of these novel complexes were successfully structurally characterized by single-crystal X-ray diffraction studies. These two series of palladium(0) complexes were tested for their potential catalytic applications in two mechanistically distinct reactions, namely, Mizoroki–Heck coupling and direct C–H functionalization reactions. One of the six-membered chelate complexes was found to be an efficient pre-catalyst for mediating the coupling reactions between aryl chlorides and alkenes. The palladium(0) complex could also be effectively applied in the direct C–H functionalization reactions of aryl bromides with 1, 2-dimethylimidazole.